Criação de um data warehouse empresarial : na direção de planeamento e gestão da TAP Portugal - Moura, André Hengeller de (2018)
Internship Report presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence